2019
DOI: 10.1177/1049909119836939
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Race and Ethnicity on End-of-Life Experiences for Children With Cancer

Abstract: Background: Racial and ethnic disparities in the provision of end-of-life care are well described in the adult oncology literature. However, the impact of racial and ethnic disparities at end of life in the context of pediatric oncology remains poorly understood. Objective: To investigate associations between end-of-life experiences and race/ethnicity for pediatric patients with cancer. Methods: A retrospective cohort study was conducted on 321 children with cancer enrolled on a palliative care service at an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…Of the 42 included studies, 11 examined the impact of specialist paediatric palliative care, 44,48,57,58,62,64,66,70,73,74,88 14 explored factors affecting access 23,43,45,56,65,68,71,75,76,[78][79][80][81][82][83]89 and 17 studies investigated both 46,47,[49][50][51][52][53][54][55][59][60][61]63,67,69,72,77,[84][85][86][87]90 (see Table 1 for study characteristics). Using the MMAT, 25 studies were categorised as quantitative non-randomised, 12 as quantitative descriptive and 5 as qualitative stud...…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Of the 42 included studies, 11 examined the impact of specialist paediatric palliative care, 44,48,57,58,62,64,66,70,73,74,88 14 explored factors affecting access 23,43,45,56,65,68,71,75,76,[78][79][80][81][82][83]89 and 17 studies investigated both 46,47,[49][50][51][52][53][54][55][59][60][61]63,67,69,72,77,[84][85][86][87]90 (see Table 1 for study characteristics). Using the MMAT, 25 studies were categorised as quantitative non-randomised, 12 as quantitative descriptive and 5 as qualitative stud...…”
Section: Study Characteristicsmentioning
confidence: 99%
“…A US study showed that black children dying from cancer more often received CPR than white children. Hispanic children less frequently received cancer therapy 28 days prior to death than non-Hispanic children [31]. Moreover, palliative care clinicians seem more reluctant to discuss prognosis with black or Latino patients with cancer than with white patients [32].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, palliative care clinicians seem more reluctant to discuss prognosis with black or Latino patients with cancer than with white patients [32]. Several explanations for these racial differences have been hypothesized, including differences in preferences regarding life-sustaining treatments, but also a lower likelihood of end-of-life preferences being discussed and honored [31].…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] Furthermore, these factors may also play a part in how AYAs and their families view illness, death, the medical system, and decisions 25,26 about the care provided at EOL. 27,28 Developmentally, it is appropriate for AYAs to start exploring what values and belief systems are important to them, which may differ from those of their family of origin. With these important elements at play, health care providers should educate themselves and seek to provide culturally humble care to ensure that AYAs' wishes are considered.…”
Section: Diversity and Cultural Considerationsmentioning
confidence: 99%
“…For many patients and families, being given the choice to plan is just as important as the location itself. AYA patients most often prioritize their relationships with others when making EOL decisions, in addition to directing their medical treatment, defining their care plans, the information their family and friends receive, and how they wish to be remembered 5–57,59–61 . Parents of critically ill children who planned the location of death achieved a home death 72% of the time compared to only 8% of those who did not plan 46 .…”
Section: Location Of End‐of‐life Carementioning
confidence: 99%